The use of metaverse in medical education: A systematic review - Qian Li; Hui Duan; Xinxu Zhou; Xiaobin Sun; Lan Tao; Xiuying Lu (Clinical Medicine)
Objective: This study aims to systematically evaluate the influence of metaverse-based teaching tools on the medical teaching effect and the improvement of students' ability, providing evidence-based support for curriculum development. Methods: A comprehensive search of PubMed, Cochrane, Embase and Web of Science databases was conducted up to 9 March 2025. Two researchers independently screened articles, extracted data, and assessed bias using the Cochrane Handbook 5.1.0 checklist. Data analysis was performed using RevMan 5.3. Results: Thirty studies involving 1,560 participants. The metaverse was applied in various areas such as surgery training, anatomy teaching and communication skills. Common metaverse approaches include AR, VR, MR etc, with simulated teaching times ranging from as little as 10 min to lasting several weeks. Most studies reported improved student guidance, reduced training time, and enhanced learning interest, and confidence. Conclusion: Metaverse technology proves effective for medical teaching, offering theoretical support for further research.